Arabic Typography Design Considerations Suitable for Wordmark Logos - Prof. Abeer Hassan Abdo; Prof. Nesrin Ezzat Gamal El din; Lect. Rania Atef Ibrahim (Journal of Architecture, Art & Humanistic Science, 2024)
The trademark is the most important element in confirming the visual identity of an organization or company. Its main function is to introduce and constantly remind it to confirm a specific idea of it. A well-designed wordmark logo is what gives a company the ability to compete, and reflects its unique personality. From here, the research problem arose in studying typography design considerations suitable for wordmark logos? Where the research aims to study the Arabic typography design considerations suitable for wordmark logos, by taking advantage of the role of the typography in creating a specific identity for it, and the researcher presents and analyzes different models for them. Since the design of the appropriate typography for the wordmark logo, is an integral part of building its identity, it has the ability to tremendously express. Fonts carry different meanings and connotations, and we automatically react differently in our thoughts, feelings, and behaviors when we see them. Thus, designing the right typography for it will convey the correct message to the recipient, while the wrong design will reduce its credibility. The research found that there is a strong relationship between memory, perception, and attention, as attention works with memory to form a distinct state of visual perception of letters and writings for the recipient, in which he identifies the structural and formal features of the typography elements, on the basis of which a corresponding formation in the memory that invokes him when he sees the same visual perceptions that Include it again.